2019
DOI: 10.1186/s13765-019-0449-x
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of perfluorinated compound content in fish cake and swimming crab by different cooking methods

Abstract: Perfluorinated compounds (PFCs) are widely used in industries, and have become common environmental pollutants. Consumption of aquatic foods and its processed products can result in the accumulation and maintenance of PFCs in organs of human body, which can lead to toxic consequences and poisoning. The aim of this study was to evaluate the reducing effects of PFC contents in fish cake and swimming crab by different cooking conditions. Fish cake was processed with blanching, boiling, frying, stir-frying and swi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 27 publications
3
14
0
Order By: Relevance
“…An LC‐MS/MS system consisting of an Agilent 1100 LC series (Agilent Technologies) equipped with an Imtackt CD‐C C18 column (2.0 mm × 150 mm, 3.0 µm particle diameter; Imtakt, Kyoto, Japan), API 4000 spectrometer (Applied Biosystems), and electrospray ionization operating in negative mode was used. Analysis was conducted following the method by Luo et al (2019). The mobile phase consists of 5 mM ammonium acetate with 0.02% formic acid in water (A) and methanol (B).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…An LC‐MS/MS system consisting of an Agilent 1100 LC series (Agilent Technologies) equipped with an Imtackt CD‐C C18 column (2.0 mm × 150 mm, 3.0 µm particle diameter; Imtakt, Kyoto, Japan), API 4000 spectrometer (Applied Biosystems), and electrospray ionization operating in negative mode was used. Analysis was conducted following the method by Luo et al (2019). The mobile phase consists of 5 mM ammonium acetate with 0.02% formic acid in water (A) and methanol (B).…”
Section: Methodsmentioning
confidence: 99%
“…The other experimental conditions used are as follows: an ion source gas 1, 40 psi; an ion source gas 2, 60 psi; an ion spray voltage of −4,500 V; and a gas temperature of 400°C. The analytical method for 19 PFCs using LC‐MS/MS was validated in terms of limits of detection (LOD) and quantification (LOQ), linearity, accuracy, and precision following the method by Luo et al (2019).…”
Section: Methodsmentioning
confidence: 99%
“…The findings of this study also revealed that the combination of pre-treatment and frying of mackerel could decrease some environmental pollutants contained in raw mackerel. Using high temperature heating and edible oil effectively reduces PFCs with high polarity in food [40,41].…”
Section: Effect Of Frying On Sensory Evaluation Of Fried Mackerel Without Batter Marinade and Spicementioning
confidence: 99%
“…Because perfluorinated compounds (PFCs) repel both water and oil, they are used as durable repellent treatments for textiles such as outdoor clothes and for home products such as carpets [1]. In addition, PFCs are widely used in the production of fluoropolymers such as polytetrafluoroethylene (trade name, Teflon), which is widely used in coatings for electronic, automotive, and outdoor products [2].…”
Section: Introductionmentioning
confidence: 99%
“…However, PFCs are harmful to both the natural environment and humans as like other well-known pollutants [1,[3][4][5][6]. Furthermore, PFCs are persistent materials that do not readily break down in natural environments [2].…”
Section: Introductionmentioning
confidence: 99%